Effect of Sodium Dehydroacetate Treatment on the Preservation and Endophyte Community Composition of Macadamia Nut - HE Peng, WANG Xiaoyu, ZHANG Tao, SONG Haiyun, CHEN Xi, ZHANG Xiufen, TANG Xiuhua, TU Xinghao, QIN Jian, WANG Wenlin (Shipin Kexue)
In this study, the effectiveness of four concentrations (0, 0.01, 0.1 and 1.0 mmol/L) of sodium dehydroacetate (SD) in prolonging the shelf life of macadamia nut was evaluated. The results showed that the quality of the untreated nut declined during postharvest storage, and both mass loss rate and decay incidence increased significantly. The storage period of macadamia nut should not exceed 16 days. Compared with the untreated control, treatment with 1 mmol/L SD solution reduced the decay rate by 23.34% after 16 days of storage. Microbiome analysis showed that the endophytic bacterium Bacillus in macadamia nut lose its dominance after being treated with 1 mmol/L SD solution, and the antagonistic relationship between endophytic bacteria and endophytic fungi decreased, thereby reducing the decay rate. The findings of this study demonstrated that 1 mmol/L SD solution could inhibit the decay of macadamia nut, improve its appearance, and prolong its shel life.